Gênero orla causo: marcas de identidade linguística do sudoeste paranaense - Chaves, Daniele Aparecida Bueno de Lima de (2019)
The present dissertation is inserted in the Linguistic Studiesfield, having Language, Education, and Work as line of research. Starting from this study area, and taking into account the theorists approached in the curriculum of the Masters in Letters of the Federal Technological University of Paraná - Campus Pato Branco, the oral genre anecdote was collected among five dwellers of different cities, by using the scientific registry, in order to analyze how the anecdotes contributed and contribute to mark the linguistic identity of Southwest Paraná. The research follows the phenomenological method, using focused interview and participant observation for recording the anecdotes. This study is divided in four chapters, aiming at the dissertation objectives. In the first one, the bases of the study development are presented, the interest in the research theme and its trajectory, as well as the problem construction, methodological orientation, and some contextual situation regarding the research subjects. In the second chapter, the theoretical bases, which guide the research, are presented. The concepts of culture, discursive genre, including the oral genre anecdote, are introduced considering the following authors: Cândido (1973), Thompson (2011), Bakhtin (2003), Bazerman (2005; 2007), Foucault (1996), Cuche (2002), Batista (2007), Santos (2010), and Eagleton (2011). Also, the concepts of language, identity, and representation are defined based on the Bakhtin/Volochinov (1997), Charaudeau(2000),Halbwachs (2006),Chauí (2006), Orlandi (2001; 2008), Hall (2011), Woodward (2014), and Silva (2014). In chapter three, the analysis categories are presented based on the anecdote fragments, which were collected and registered. They reveal the technics used by each anecdote teller to create effects of truth, and to make possible links between anecdotes of different themes. Also, some emotion marks are examined, including the most mentioned themes among the five participants. In final considerations, the interdisciplinary features of the study are highlighted, emphasizing the relation among language, identity, culture, and representation, affirming the possible contributions of the present research to the education area.